Quantifying the local-scale ecosystem services provided by urban treed streetscapes in Bolzano, Italy (2016)
Urban green infrastructure has the potential to offer multiple ecosystem services to society. However, there is little information about the role of these tree dominated, public streetscapes on the local-scale provision of ecosystem services in European mid-sized cities. In the present study, we explored the local-scale effects of different tree dominated streetscape types on mitigating temperatures and air pollution in the city of Bolzano, Italy by integrating the ENVI-met and UFORE models as well as local field, pollution and climate data. We found that total estimated air pollution removal by trees in Bolzano was 2.42 metric tons per year (t/yr); with ozone (1.2 t/yr) being the pollutant most removed and carbon monoxide (0.03 t/yr) the least. Total air pollution removal (901.4 kg/yr) was greatest in parks. Total biogenic volatile organic compound emissions, an ecosystem disservice, were also estimated. The ENVI-met simulations found that urban trees can reduce streetscape temperatures by up to 2 °C during the summer and improve human thermal comfort. Results can be used to better understand the dynamics of local-scale ecosystem services of mid-size European cities and to better assess the role of urban streetscapes and green infrastructure in improving human well-being and mitigating the effects of climate change.